The Subjectivity Argument: An A Priori Argument for the Incarnation - Sijuwade, Joshua (AGATHEOS – European Journal for Philosophy of Religion, 2025)
This article focuses on providing a new a priori argument for the veracity of the doctrine of the Incarnation. This new argument, called the Subjectivity Argument, will be formulated in light of the concept of “omnisubjectivity,” as proposed by Linda Zagzebski, and an “emotion,” as conceptualised by the “somatic feeling theory,” posited by Jesse Prinz. Doing this will provide a specific argument that provides strong grounds for affirming the necessity of the Incarnation, without, however, being subject to the primary objections that can be raised against other a priori arguments for the Incarnation in the contemporary literature.